Does Energy Drink Provokes Gait Modifications in Young Healthy Adults? - Rosario, Martin G; Hogle, Jason; Williams, Brooks (Journal of Sports Research, 2021)
Energy drinks have become increasingly popular among young adults and athletes in the last few years. Despite their popularity, little research has substantiated the claims of the positive effects on physical performance of popular energy drinks. Most current research focuses on caffeine alone, but does not often look at how mixing it with other psychoactive substances might alter its effects. Purpose: This study aimed to determine the alterations of gait tasks after consumption of three popular energy drinks on young healthy adults. Methods: Fifteen women and five men were recruited, screened, and signed informed consent to participate in this study. All participants were healthy young adults with no apparent comorbidities that might have been impacted by the consumption of energy drinks. Motion analysis was conducted using Movement Lab TM sensors placed at key anatomical points. Subjects were asked for two bouts of gait tasks pre-energy drink consumption, and then repeat the same tasks after energy drink consumption. Results: There were no significant modifications in gait, however, observable trends were detected in postural gait parameters following the consumption of a Rockstar energy drink. Conclusion: We infer that the trends observed could be attributed to the specific key ingredients used in Rockstar and might have caused gait deviations post consumption. Further studies should focus on Rockstar alone and its specific key ingredients of caffeine, guarana, ginseng, and milk thistle to determine their influence on gait deviations.